'Trapped rainbow' schemes for storing light in engineered waveguides - K. L. Tsakmakidis; Hess, O. (Optics InfoBase Conference Papers, 2009)
We review recent progress in the realm of ultra-slow and stored light inside metamaterial waveguides. We elucidate a number of critical issues pertaining to the study of light propagation in various slowlight metamaterial structures. © 2008 Optical Society of America.
cited By 0